Linking Education, Culture and Community: A Proposal for an Intercultural Educational Triad - Gerardo Fuentes-Vilugrón; Eduardo Sandoval-Obando; Daniella Landeros-Guzmán; Lorena Elizabeth Pérez-Quinteros; Carlos Arriagada-Hernández; Felipe Caamaño-Navarrete; Paulo Etchegaray-Pezo; Pablo del Val Martín; Lorena Jara-Tomckowiack; Gerardo Muñoz-Troncoso; Flavio Muñoz-Troncoso (Education Sciences, 2025)
Introduction: Engaging social actors dedicated to education has facilitated dialogue, emotional connection, action, and the accumulation of knowledge to create insights that address community needs and promote its development. This study aims to understand the relationship between education, culture, and community as described by teachers working in Mapuche contexts in the Araucanía region of Chile. Method: This research was based on social science research, using a qualitative approach and a non-experimental emergent design. The participants interviewed for the study consisted of 15 in-service teachers in three schools in Mapuche contexts in the Araucanía region of Chile. The study used a semi-structured interview script to collect data, and in the analysis plan the Grounded Theory (GT) was used, to conceptualize the emerging patterns in categorized concepts and theories. Results: The analysis revealed three distinct categories: culture and diversity; education; and community. Discussion: There is a connection between culture and diversity, education, and community, with learning as the central theme. However, each of these dimensions tends to operate mainly in isolation, lacking effective connections that would facilitate consistent development in the learning and teaching processes. Conclusions: It is essential to incorporate inclusive strategies that recognize and value social and cultural diversity within school classrooms and promoting the dialogue of knowledge and wisdom through intercultural education fosters the active participation of all actors involved in the teaching and learning processes.